Assessment of the contribution of TEX air pollutants from Nigeria's petroleum refineries to the ambient air quality: Part II. Issue 1 (1st January 2021) - Odekanle, Ebenezer Leke; Bakut, Chinchong Blessing; Olalekan, Abiodun Paul; Ogundokun, Roseline Oluwaseun; Aremu, Charity O.; Sonibare, Jacob Ademola; Akande, Oreoluwa Tabitha; Olayanju, Adeniyi Tajudeen; Fakinle, Bamidele Sunday
Abstract: Environmental hazards associated with release of emission from petroleum refineries have caused serious concerns for the host communities. The study focused on the assessment of the contribution of Nigerian refineries to the ambient air quality. Total emission of toluene, ethyl benzene and xylene (TEX) from Nigerian twenty-six (four existing and twenty-two proposed) refineries were estimated using emission factor approach, under no-control measure (worst case scenario) option. Results showed that the four existing refineries emit 2.90 × 10 13 tons of toluene, 1.93 × 10 13 tons ethyl benzene and 1.06 × 10 13 tons per year while the twenty-two proposed refineries have the capacity of releasing annually 9.17 × 10 13 tons of toluene, 6.69 × 10 13 tons of ethyl benzene and .95 x 10 13 tons of xylene. If operated at full capacity, the total estimated TEX emission from the existing refineries stood at 5.89 × 10 13 tons/year while the proposed refineries have the potential of adding additional 2.01 × 10 14 tons/year. These concentrations were considered as environmental menace that could have adverse health challenge of the residents of the host communities. Some technologically driven measures to control and subsequently reduce TEX emission from these refineries were suggested.